Theoretical Modelling of Portable Vertical Axis Wind Harvesting System - Lew, Heng Loong; Ching, Kok Boon (Evolution in Electrical and Electronic Engineering, 2021)
As the depletion of fossil-fuel resources is exacerbated due to the increasing power demand of industries and transportation, harnessing wind energy is essential to replace non-renewable energy in generating energy. Moreover, the low annual wind speed in Malaysia is one of the factors that increases the difficulty of harnessing wind energy in generating electrical energy. In this paper, a portable vertical axis wind energy harvesting system (VAWEHS) that can extract energy from wind with low speed is presented for the application of high-rise buildings. Savonius wind turbine which is a type of vertical axis wind turbine (VAWT) is modelled based on related equation in converting wind energy to electrical energy, and the performance of system is further enhanced by permanent magnet DC generator (PMDCG), boost converter, bidirectional converter, and DC-link voltage control scheme. In MATLAB/SIMULINK simulation with a duration of 100 seconds, the proposed VAWEHS can provide a maximum output voltage of 18.5 across a 10.8 load and store a portion of electrical energy into a lead-acid battery under wind speeds of 1.667 m/s, 2.500 m/s, 3.611 m/s, 5.278 m/s, and 6.667 m/s. It is also capable to supply a current of 1.7A at the voltage of 18.5 V with the help of boost converter during the discharging process. It is concluded that the proposed design of VAWEHS can perform well in generating electrical energy by harnessing wind energy. In future, the system can be further improved by introducing advanced control schemes